What are effective strategies to communicate cardiovascular risk information to patients?: a systematic review - Waldron, Cherry-Ann; van der Weijden, Trudy; Ludt, Sabine; Gallacher, John; Elwyn, Glyn (Patient education and counseling, 2011)
Objective - To compare different interventions used to communicate cardiovascular risk and assess their impact on patient related outcomes. - Methods - A systematic search of six electronic data sources from January 1980 to November 2008. Data was extracted from the included studies and a narrative synthesis of the results was conducted. - Results - Fifteen studies were included. Only four studies assessed individuals’ actual cardiovascular risk; the rest were analogue studies using hypothetical risk profiles. Heterogeneity in study design and outcomes was found. The results from individual studies suggest that presenting patients with their cardiovascular risk in percentages or frequencies, using graphical representation and short timeframes, is best for achieving risk reduction through behaviour change. However, this summary is tentative and needs further exploration. - Conclusion - Better quality trials are needed that compare different risk presentation formats, before conclusions can be drawn as to the most effective ways to communicate cardiovascular risk to patients. - Practice implications - Instead of directing attention to the accuracy of cardiovascular risk prediction, more should be paid to the effective presentation of risk, to help patients reduce risk by lifestyle change or active treatment.
Online verfügbar 14 May 2010
Gesehen am 04.11.2022